Economics as a social science : an approach to nonautistic theory - Kamarck, Andrew M. (University of Michigan Press, 2002)
"Economics as a Social Science: An Approach to Nonautistic Theory, a highly readable critique of economic theory based on a wide range of research, endeavors to restore economics to its proper role as a social science. Contrary to conventional economic theory, which assumes that people have no free will, this book instead bases economics on the realistic assumptions that human beings can choose; that we are complex beings affected by emotion, custom, habit, and reason; and that our behavior varies with different circumstances and times. It embraces the findings of history, psychology, and other social sciences, as well as the insights from great literature on human behavior, rejecting the rigid mathematical axioms that define how economics is understood and practiced today."--Jacket